2023
DOI: 10.3390/cancers15133464
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role for Sigma Receptor 1 in Personalized Treatment of Breast Cancer

Abstract: Despite the major progress in treating breast cancer, recurrence remains a problem and types such as triple-negative breast cancer still lack targeted medicine. The orphan Sigma receptor1 (SigmaR1) has emerged as a target in breast cancer, but its mechanism of action is unclear and hinders clinical utility. SigmaR1 is widely expressed in organ tissues and localized to various sub-cellular compartments, particularly the endoplasmic reticulum (ER), the mitochondrial-associated membranes (MAMs) and the nuclear en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…These findings highlight the potential role of S1R in these diseases. Several studies have demonstrated a tumor-promoting role for S1R [59,60]. If S1R protects cells from ferroptosis, the tumor-promoting effect of this receptor makes sense.…”
Section: Protection Against Ferroptosis By S1r and Its Relationship T...mentioning
confidence: 99%
“…These findings highlight the potential role of S1R in these diseases. Several studies have demonstrated a tumor-promoting role for S1R [59,60]. If S1R protects cells from ferroptosis, the tumor-promoting effect of this receptor makes sense.…”
Section: Protection Against Ferroptosis By S1r and Its Relationship T...mentioning
confidence: 99%